The Risk of Hypertension and Other Chronic Diseases: Comparing Smokeless Tobacco with Smoking - Anand, Ankit; Sk, Md Illias Kanchan (Frontiers in Public Health, 2017)
Background: In the past, studies have compared smokeless tobacco and non-tobacco users for the risk of various chronic diseases. The differences in the risk of chronic diseases between smokeless tobacco user and smokers have not been explored. The objective of this study is to estimate the risk of chronic diseases among smokeless tobacco users compared to smokers. Methods: The data was used from the Study on Global Ageing and Adult Health (SAGE) Wave-1, conducted in 2007-08 in India. The study sample are the respondents who reported consuming any form of tobacco in last one month. The total sample size was 4038 respondents. The odds ratio of chronic morbidities was estimated taking smokers as the reference category. Results: The odds ratios for (self-reported) Diabetes, Asthma, and Hypertension were not significant for smokeless tobacco user compared to smoked tobacco users. The odds ratio of chronic lung diseases was significantly lower among smokeless tobacco users compared to smoked tobacco users. The odds ratio of Hypertension (measured) combined with low education and belonging to lowest wealth quintiles were not significant for smokeless tobacco users compared to smoked tobacco users. Duration of the use of smokeless tobacco and quantity of use was found to have no significant relation with risk of chronic diseases as compared to smoking Conclusion: This study did not find the significantly higher risk of chronic morbidities except for chronic lung disease for smokeless tobacco users compared to smoked tobacco users. The study suggests that the use of any form of tobacco may have a similar risk of chronic diseases.